Antecedents of innovation in industry: The impact of work environment factors on creative performance. Issue 3 (16th July 2018) - Ramos, Marco Andre Wiley; Figueiredo, Paulo S.; Pereira-Guizzo, Camila
Abstract : Purpose: Today, organizations must be able to create innovative strategies, and creative performance depends on knowing what hinders or stimulates creativity. This paper aims to determine which factors in the workplace environment positively or negatively affect creativity by analyzing individuals' perceptions in a sample of Brazilian industrial companies. Design/methodology/approach: The discussion is based on the componential theory of creativity and the use of a recognized research instrument (KEYS). A regression analysis was carried out, using eight environmental factors related to creativity. The purpose of the collection is to observe the statistical relationships between the scales of the factors and the results related to creativity. Findings: Among the eight factors of the original componential theory, only three were found to have a significant impact on the creative process: organizational incentives, challenging work and support from the work group. Research limitations/implications: The sample in this study was relatively small, and a larger sample will be required to undertake factor analysis. Practical implications: Possible implications for the management of innovation in the Brazilian context are discussed in light of these results. Originality/value: This study contributed to the production of knowledge, still scarce in the country, about the search for creative solutions through the work environment by confirming which factors are significant and determinants of creative performance and challenging factors that had already been proven by other studies in non-Brazilian contexts.